Temporal and Spatial Analysis of the Occupational Noise at Rice Mill in Kedah - Mansor A.A.; Abdullah S.; Ahmad Nawawi M.A.; Ahmed A.N.; Mohd Napi N.N.L.; Ismail M. (Institute of Physics Publishing, 2023)
Accident prevention; Audition; Human resource management; Machinery; Noise pollution; Occupational risks; Risk assessment; Sustainable development; Company management; Negative correlation; Occupational hazards; Occupational noise; Occupational safety and health; Safety and healths; Temporal and spatial; Working environment; Acoustic noise